2013
DOI: 10.1111/ans.12309
|View full text |Cite
|
Sign up to set email alerts
|

Vascular trauma in Western Australia: a comparison of two study periods over 15 years

Abstract: Background: Royal Perth Hospital (RPH) has become Western Australia's only designated adult major trauma facility since a previous study of vascular trauma was conducted in 2001 at the same facility. The aim of this study is to identify changes in vascular trauma patterns over the two study periods and compare these changes with international literature. Methods: All individuals presenting to RPH between January 2000 and December 2010 with vascular injury were identified from a prospective trauma database for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 17 publications
8
17
1
6
Order By: Relevance
“…Blunt trauma accounted for majority of these cases in this study which is similar to an Australian study [6]. The percentage of blunt trauma is very high-46 of 49 trauma (93.8 %) cases-in this series compared to any study, probably due to lower incidence of gunshot and stab injuries.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Blunt trauma accounted for majority of these cases in this study which is similar to an Australian study [6]. The percentage of blunt trauma is very high-46 of 49 trauma (93.8 %) cases-in this series compared to any study, probably due to lower incidence of gunshot and stab injuries.…”
Section: Discussionsupporting
confidence: 85%
“…All the reported series in literature are institutional and none of these are single-surgeon experience; this is to date is the first largest, single-surgeon experience series. Young men in productive age group (mean age 28 years) account for large number of patients as in the case of any trauma, which correlates with other studies [3,5,6]. Many of these patients are breadwinners of the family, and outcomes of arterial injury can have a major impact on the economy in addition to the health care burden.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Del 60 al 90% de las lesiones civiles en el tronco o las extremidades son secundarias a mecanismos penetrantes, generalmente por armas de fuego. Las lesiones por trauma cerrado son infrecuentes, por lo general en pacientes de mayor edad; al implicar mecanismos de mayor fuerza y velocidad, se asocian con lesiones intrabdominales, torácicas, de tejidos blandos u óseos [2][3][4][5] .…”
Section: Introductionunclassified
“…1 The most recent Australian study at high volume centre found that vascular trauma accounted for 3.2% of all trauma admissions and was increasing over time. 2 Furthermore, the literature suggests that the mortality rate of vascular trauma lies between 18 and 26%. [3][4][5] Given that this is dramatically higher than the mortality for overall trauma reported in Australia it is clear that vascular trauma and its treatment are a crucial aspect of trauma management at any institution.…”
Section: Introductionmentioning
confidence: 99%